Alzheimer's Aβ peptides with disease-associated N-terminal modifications: influence of isomerisation, truncation and mutation on Cu2+ coordination. - Simon C Drew (PLoS ONE, 2010)
BACKGROUND: The amyloid-β (Aβ) peptide is the primary component of the extracellular senile plaques characteristic of Alzheimer's disease (AD). The metals hypothesis implicates redox-active copper ions in the pathogenesis of AD and the Cu(2+) coordination of various Aβ peptides has been widely studied. A number of disease-associated modifications involving the first 3 residues are known, including isomerisation, mutation, truncation and cyclisation, but are yet to be characterised in detail. In particular, Aβ in plaques contain a significant amount of truncated pyroglutamate species, which appear to correlate with disease progression. METHODOLOGY/PRINCIPAL FINDINGS: We previously characterised three Cu(2+)/Aβ1-16 coordination modes in the physiological pH range that involve the first two residues. Based upon our finding that the carbonyl of Ala2 is a Cu(2+) ligand, here we speculate on a hypothetical Cu(2+)-mediated intramolecular cleavage mechanism as a source of truncations beginning at residue 3. Using EPR spectroscopy and site-specific isotopic labelling, we have also examined four Aβ peptides with biologically relevant N-terminal modifications, Aβ1[isoAsp]-16, Aβ1-16(A2V), Aβ3-16 and Aβ3[pE]-16. The recessive A2V mutation preserved the first coordination sphere of Cu(2+)/Aβ, but altered the outer coordination sphere. Isomerisation of Asp1 produced a single dominant species involving a stable 5-membered Cu(2+) chelate at the amino terminus. The Aβ3-16 and Aβ3[pE]-16 peptides both exhibited an equilibrium between two Cu(2+) coordination modes between pH 6-9 with nominally the same first coordination sphere, but with a dramatically different pH dependence arising from differences in H-bonding interactions at the N-terminus. CONCLUSIONS/SIGNIFICANCE: N-terminal modifications significantly influence the Cu(2+) coordination of Aβ, which may be critical for alterations in aggregation propensity, redox-activity, resistance to degradation and the generation of the Aβ3-× (× = 40/42) precursor of disease-associated Aβ3[pE]-x species.